EFFORTS TO ADDRESS SMOKING'S IMPACT THROUGH EDUCATION USING SHORT FILMS, SMOKER TESTIMONIALS, AND SIMULATIONS OF ITS EFFECTS ON LUNG HEALTH - Hilmi, Moh. Mustofa; Nuria, Ervina Shinta; Primasti, Resta; Febrilia, Zhania Fitri; Nursyafa'ati, Hesti Puji; Yustisia, An Nisa; Putri, Nabila Haynaya; Hiadayah, Eva Nur; Fadlia, Mincha; Orchita, Novenda Salma; Utami, Adelia Yunika; Ratnawati, Ratnawati; Prasetijono, Purwito Soegeng; Suparmi, Suparmi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Smoking behavior is the act of inhaling smoke from burning tobacco and then exhaling it. This community service (PkM) project aims to educate residents of RW 11, Bangetayu Kulon Village, Semarang City, about the effects of smoking through a short film, testimonials from former smokers, and a simulation demonstrating the impact of smoking on lung health. The intervention was attended by 56 participants and included the following activities: (1) health checks, which involved measuring blood pressure and conducting random blood sugar tests; (2) a pre-test to assess participants’ knowledge of smoking hazards using a questionnaire; (3) screening of the short film; (4) a health education session on the dangers of smoking; (5) a simulation using simple tools to help participants better understand smoking hazards; (6) a testimonial interview with a former smoker; and (7) a post-test to evaluate participants' knowledge levels. The success of the education initiative was measured with a questionnaire consisting of ten questions for participants. The evaluation indicated that the PkM team's efforts significantly enhanced participants' knowledge (p<0.05). Pre-intervention scores (pre-test) averaged 80.17±9.24, while post-intervention scores (post-test) averaged 94.82±6.6, reflecting an 18.27% increase in knowledge among the RW 11 residents of Bangetayu Kulon Village. Ideally, family members and stakeholders should follow up on this PkM outcome to monitor adherence to smoking cessation.